Wybrane wskaźniki oceny efektywności działania firmy kurierskiej - Lejda, Kazimierz; Siedlecka, Sylwia (Видавництво Львівської політехніки, 2018)
Efficiency evaluation among other factors, which affect the functioning of delivery companies, have been presented in the article. Selected performance indicators, as they rest on the comparison of brought contributions to gained effects have been described. Thus, such an assessment requires a selection of appropriate parameters that accurately reflect real condition.
Selected indicators of the efficiency evaluation of delivery companies
Keywords: 656.025